Consequences of Groundwater‐Model Vertical Discretization in Risk‐Based Decision‐Making. Issue 5 (20th November 2019) - White, Jeremy T.; Knowling, Matthew J.; Moore, Catherine R.
Abstract: One of the first and most important decisions facing practitioners when constructing a numerical groundwater model is vertical discretization. Several factors will influence this decision, such as the conceptual model of the system and hydrostratigraphy, data availability, resulting computational burden, and the purpose of the modeling analysis. Using a coarse vertical discretization is an attractive option for practitioners because it reduces data requirements and model construction efforts, can increase model stability, and can reduce computational demand. However, using a coarse vertical discretization as a form of model simplification is not without consequence; this may give rise to unwanted side‐effects such as biases in decision‐relevant simulated outputs. Given its foundational role in the modeled representation of the aquifer system, herein we investigate how vertical discretization may affect decision‐relevant simulated outputs using a paired complex‐simple model analysis. A Bayesian framework and decision analysis approach are adopted. Two case studies are considered, one of a synthetic, linked unsaturated‐zone/surface‐water/groundwater hydrologic model and one of a real‐world linked surface‐water/groundwater hydrologic‐nitrate transport model. With these models, we analyze decisions related to abstraction‐induced changes in ecologically important streamflow characteristics and differences in groundwater and surface‐water nitrate concentrations and mass loads following potential land‐use change. We show that for some decision‐relevant simulated outputs, coarse vertical discretization induces bias in important simulated outputs, and can lead to incorrect resource management action. For others, a coarse vertical discretization has little or no consequence for resource management decision‐making. Abstract : Article impact statement : Groundwater model vertical discretization is shown to be important in some decision‐making contexts but not in others.